Evaluation of the role of Islamic lifestyle in communication skills of Muslim couples - Zuhri, Ahmad (HTS teologiese studies, 2023)
Lifestyle refers to a set of personal and group behaviours related to normative and semantic aspects of social life. Any coherent set of behavioural patterns derived from religious teachings that exist in life can be considered a religious lifestyle. Considering that the dominant religion in Jordan is Islam, the present study focused on the Islamic lifestyle. In addition, given that the correct relationship between couples has been compared to life-giving blood in marriage, and since the quality of marital role plays a determining role, the existence of communication skills in any of the couples can generate satisfaction and compatibility, whereas lack of awareness of these skills could cause misunderstandings and tension. Therefore, the current study aims to study the role of the Islamic lifestyle in communication skills of 250 Muslim couples of Jordan (Amman, Zarqa and Irbid) in 2022. Data were collected using questionnaires during four months, and the validity and reliability was confirmed. In addition, data analysis was performed in Statistical Package for Social Sciences (SPSS) and Linear Structural Relations (LISREL) using mean tests and structural equation modelling. According to the results, Islamic lifestyle had a positive, significant effect on the improvement of communication skills in Muslim couples in Jordan (P-value: 0.76; T-value: 7.92). Therefore, it is recommended that more attention should be paid to this issue by families, researchers and cultural authorities in the country.Contribution: Our findings revealed that Islamic lifestyle improved communication skills in Muslim couples, which demands special attention. By adhering to the Islamic lifestyle, couples can influence each other’s knowledge, emotions, education and growth, and try to have a realistic understanding of each other’s desires, needs, living environment and perceptions that each has in life issues. Furthermore, they can organise their role in the common life in appropriate ways to prevent problems and solve them in the event of problems.